INVESTIGATING THE ROLE OF EPIGENETICS IN CANCER DEVELOPMENT AND THERAPY (Journal of Medical & Health Sciences Review, 2025)
Background: Cancer is a multifactorial disease influenced by genetic and epigenetic alterations. Epigenetics, which involves heritable changes in gene expression without altering the DNA sequence, plays a critical role in cancer development and progression. Recent advancements in epigenomic technologies have enhanced our understanding of the mechanisms underlying epigenetic modifications and their therapeutic potential.Objective: This study investigates the role of epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNAs, in cancer development and explores the application of epigenetic therapies in clinical settings.Methodology: A comprehensive analysis was conducted using next-generation sequencing (NGS) and bioinformatics tools such as Illumina BaseSpace, and methylation-specific PCR (MSP). Publicly available databases, including TCGA (The Cancer Genome Atlas) and ENCODE, were utilized to identify cancer-specific epigenetic alterations. Statistical analyses were performed using R software (v4.2.1) and the Bioconductor package. Functional validation of key epigenetic targets was achieved through CRISPR-dCas9 epigenetic editing in cancer cell lines.Results: The study identified significant hypermethylation of tumour suppressor genes (e.g., CDKN2A and BRCA1) and hypomethylation of oncogenes (e.g., MYC) in various cancers. Histone acetylation was found to regulate the expression of genes associated with tumour metastasis. Non-coding RNAs, such as miR-21 and lncRNA-HOTAIR, were implicated in modulating cancer cell proliferation and apoptosis. Epigenetic therapies, including DNA methyltransferase inhibitors (e.g., azacitidine) and histone deacetylase inhibitors (e.g., vorinostat), showed promising results in reversing aberrant epigenetic marks, enhancing chemosensitivity, and reducing tumour growth.Conclusion: Epigenetic modifications play a pivotal role in cancer development by altering gene expression patterns and promoting tumorigenesis. The integration of epigenomic profiling with advanced bioinformatics tools provides valuable insights into potential therapeutic targets. Epigenetic therapies, when combined with conventional treatments, hold significant promise in improving cancer management and patient outcomes. Further research is warranted to optimize these approaches and overcome current challenges in clinical translation.